Officialdom of the Tuvan people’s republic: transformation of the socio-cultural - Khovalyg, Salimaa S. (Opción, 2019)
The article aims to the problems of the transformation of the socio-cultural image of officialdom during the period of the Tuvan People’s Republic (1921-1944). The author on the basis of the analysis of archival sources reveals the problems of transforming the socio-cultural appearance of officialdom in the period of the formation and development of a sovereign state. As a methodological basis for the study, the principles of historicism, the method of comparative historical analysis were used. The author reveals the transformation of the socio-cultural image of Tuvan officials on the examples, external and internal factors that influenced this process.